NONTHERMAL PLASMA: A REVIEW ON ITS PROSPECTS ON FOOD PROCESSING - Gede Arda; Chuang Liang Hsu (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2020)
Bringing plasma into food processing is a relatively new measure for food engineer and scientist. It is simple in generation, low energy requirement, high efficacy, and easy to apply, pave its way to be a new prospective scenario in processing more safety food recently. Plasma is the fourth matter after solid, liquid and gas contain various reactive species generated by electrical discharge from 10-120kV. Those are Reactive Oxygen and Nitrogen (RONS) comprising various reactive species including nitric oxide (NO), superoxide (O2-), hydrogen peroxide (H2O2); singlet oxygen (1O2); ozone (O3) and even hydroxyl radical (-OH) which can and do play important roles in biological systems. This brief review describes plasma interaction with the biological system and pesticides compound and sums up some finding on the nonthermal application on two main consideration of food safety namely microorganisms decontamination and pesticides residue degradation.